(untitled) (Journal of the College of Basic Education, 2022)
The present study introduces description of a new recordes species of insects belong to the genus Cercopis Rossi, 1807 (Homoptera: Cercopidae). External morphological characters particularly male and female genetalia were discussed and illustrated. Locality and date of collection were given.